Pengaruh tenaga kerja dan PAD terhadap pertumbuhan ekonomi serta dampaknya terhadap kemiskinan di Kabupaten Ngawi - Kiki Nurtia Sibolga Marbun; Muchtolifah . (Universitas Negeri Surabaya, 2023)
For the past 10 years, Ngawi Regency has remained in the top 10 poverty zones in East Java Province, indicating that the welfare of the people in Ngawi Regency is still very low. The main objective of this study is to examine how variations in the number of working people and the level of regional income contribute to economic growth and subsequently affect the poverty rate. This study uses quantitative analysis and statistical techniques to analyze relevant data collected from Ngawi Regency. The population in this study used Ngawi Regency with research samples of Labor, Regional Ali Revenue (PAD) and Economic Growth. The results of this study indicate that Labor directly has a positive and significant effect on the Poverty Level. PAD directly has a negative and significant effect on the Poverty Level. Labor and PAD indirectly have no effect on the Poverty Level through Economic Growth. Economic Growth directly has a positive and insignificant effect on the Poverty Level. These findings can be used to inform policy-making decisions and develop effective strategies for poverty alleviation and sustainable development in the region.